A Needs Analysis of English for Specific Purposes (ESP) for Biology Students - Roni Sofyan Hadi; Ari Prasetyaningrum; Siti Maysuroh; M. Adib Nazri (Jurnal Ilmiah Profesi Pendidikan, 2026)
General English curricula often fail to equip non-English science majors with essential disciplinary vocabulary, leaving biology students unprepared for the global scientific community. This study aims to conduct a comprehensive needs analysis to identify the specific English learning needs and contextual linguistic barriers of undergraduate biology students. Employing a descriptive qualitative design, empirical data were collected from 31 Biology students at Hamzanwadi University through digital questionnaires and structured in-depth interviews. The findings reveal that students experience severe communicative paralysis when explaining biological concepts due to the morphological complexities of Latin nomenclature, heavily relying on digital translation tools. Conversely, their professional demands are highly specific, requiring skills to translate scientific abstracts, sharp listening for seminars, and tailored materials focusing on biotechnology. This study concludes that standard General English is fundamentally inadequate, mandating an urgent institutional pivot toward a tailored English for Specific Purposes (ESP) syllabus to align learning with industry standards.